Senyawa Antimalaria dari Jamur Endofitik Tumbuhan Sambiloto (Andographis paniculata Nees) - Elfita, Elfita; Muharni, Muharni; Munawar, Munawar; Salni, Salni; Oktasari, Ade (Jurnal Natur Indonesia, 2011)
Plants have been the chief source of compounds of medicine for thousand of years. Plants are also the source ofmany medicines for the majority of the world’s population. The role of biotechnology is very important for multiplying,conserving the spesies, and enhancing the production of secondary metabolites. Endophytic are microbes thatinhabit plants are currently considered to be a wellspring of novel secondary metabolites offering the potensial formedical and industrial exploitation. Plants with ethnobotanical history, for example sambiloto (Andographispaniculata Nees) are likely candidates for finding bioactive compounds. Isolation begin with cultivation of Aspergillusflavus fungi in 2 liter of Potato Dextrose Broth media for four weeks. Media is extracted into the solvent n-hexaneand ethylacetate following by evaporation. Ethylacetate extracts were separated by chromatography techniquesin order to get pure compound in the form of white crystal. Phytochemical tests showed that the isolated compoundis alkaloid. The molecular structure of the isolated compound was determined based on spectroscopic data,including UV, IR, 1H-NMR, 13C-NMR, HMQC, and HMBC spectrum. The compound was determined as7-hydroxypiranopiridin-4-on with molecule formula C8H7NO2 (Mr=149). The compound has antimalarial activityagainst Plasmodium falciparum 3D7, with IC50 values 0,201 μM.